De aluno a formador: uma vivência de agência transformativa compartilhada - Oliveira, Vinicius Soares de (2023)
The planning and action of teacher education should lead to transformations in pedagogical practice and in the surrounding social, political and economic context. The pandemic context and its consequences, not yet fully understood, have imposed relevant challenges to the teacher education process. Thus, the main question of this investigation was the question: how to plan and execute, in many hands, a critical-collaborative training process, based on the desire for social change and ethical-political principles, whether in a face-to-face or remote model? Based on the mobilizing question, we thought of the objective as being: to analyze, through procedures of description, information, confrontation, and reconstruction, the planning and training activities proposed by the "Projeto Brincadas: o inédito viável em tempos de crise". Specifically, we focused on a live called "Hora da Brincada", about engaged multiliteracy and feminine power through the parameters of language typical of critical reflection. The research was mostly conducted in a pandemic context, which required flexibility and creativity. The data were obtained in the aforementioned "Hora da Brincada" as an observer and in the collective construction of a didactic proposal with fellow researchers participating in the discipline of "Engaged Multiliteracy: in the Training of Educators and Trainers". The data analysis was performed from the methodology proposed by Liberali (2018) from the language of critical reflection and its acts, namely, describe, inform, confront, and reconstruct. As a theoretical reference, the historical-dialectical materialism, the notion of shared transformative agency, and the perspective of critical-collaborative training were adopted. The results point to the need to expand the processes of planning and formative action beyond the technical language, information transmission practices, incorporating ethical and political aspects and the desire for social transformation